Strategi Komunikasi Persuasif pada Konten Self-Development di Akun Instagram @ananzaprili - Diah Retno Ningsih (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
In today's digital age, social media has become an effective platform for conveying messages and influencing audience behavior, with Instagram being a prime example. Persuasive communication is a key strategy for delivering messages that can motivate, inspire, and shift the mindset of audiences. One content creator who actively shares self-development messages is @ananzaprili, who employs persuasive communication techniques to capture audience attention. This research aims to analyze the application of persuasive communication techniques in self-development content published by content creator @ananzaprili. Employing a descriptive qualitative method and drawing upon Carl Hovland's persuasive communication theory, this study identifies various persuasive strategies such as association, integrity, rewards/incentives, arrangement, and red-herring. The persuasive communication strategies implemented by @ananzaprili enhance audience engagement and encourage positive behavioral changes related to self-development. Furthermore, the use of engaging language that fosters active involvement with followers is a key factor in the success of this strategy.